2013
DOI: 10.1002/pbc.24869
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan and temozolomide for treatment of neuroblastoma in a patient with renal failure on hemodialysis

Abstract: Renal failure is a rare complication of neuroblastoma or its therapy. To our knowledge, no reports describe treatment of children with neuroblastoma with chemotherapy in the setting of renal failure and maintenance hemodialysis. We report a 6-year-old child with high-risk neuroblastoma who developed renal failure requiring long-term hemodialysis. She was subsequently treated with 13 cycles of intravenous irinotecan 20 mg/m(2)/day and oral temozolomide 100 mg/m(2)/day for 5 days before disease progression witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Several reports have described patients with high-risk neuroblastoma developing renal failure,5 but no reports are available on HDCT with auto-PBSCT in a pediatric patient with neuroblastoma under ESRD. Armstrong et al6 prescribed consolidation treatment with irinotecan and temozolomide for their patient with high-risk neuroblastoma requiring maintenance HD. The patient safely underwent consolidation therapy, but the disease progressed after several months.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described patients with high-risk neuroblastoma developing renal failure,5 but no reports are available on HDCT with auto-PBSCT in a pediatric patient with neuroblastoma under ESRD. Armstrong et al6 prescribed consolidation treatment with irinotecan and temozolomide for their patient with high-risk neuroblastoma requiring maintenance HD. The patient safely underwent consolidation therapy, but the disease progressed after several months.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have confirmed that patients with chronic renal failure (CRF) have a higher incidence of malignant tumors and mortality[ 4 , 5 ]. When the estimated glomerular filtration rate (GFR) drops to 10 mL/min/1.73 m 2 , the mortality rate of cancer patients increases by 22%[ 6 , 7 ]. Therefore, the reduction in GFR will not only lead to serious renal complications, but also limit the treatment of tumors, thereby promoting tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…These patients generally have a high mortality. The mortality rate of a cancer patient increases by 22 % when the estimated glomerular filtration rate (GFR) decreases to 10 mL/min/1.73 m 2 [ 1 , 2 ]. This finding can be attributed to the fact that GFR reduction not only induces severe kidney complications but also restricts tumor treatment, thereby promoting tumor progression.…”
Section: Introductionmentioning
confidence: 99%